Dynamic Analysis of the German Day-Ahead Electricity Spot Market - Marius Paschen (University of Oldenburg, Department of Economics, 2014)
This paper analyzes the dynamic behavior of day-ahead spot prices in the German electricity spot market due to positive structural shocks in wind and solar power. It uses a dynamic structural vector autoregressive model to estimate the related structural impulse response functions. The estimates suggest that wind power shocks have a more prolonged negative effect on spot prices than solar power shocks. These may be explained by signifcant autocorrelations of wind power for larger lags. The total negative merit order effect of a solar power shock, however, is larger. One reason might be that solar power shocks coincide with demand peaks. Past empirical results show differences in the total average negative merit order effects. The inherently dynamic nature of wind and solar power could explain these dfferences because the dynamics, which are ignored by past studies on the subject using static ordinary least squares estimations, could be transferred to the merit order effects.
Keywords: Q42; Q41; C32; C51; 330; Electricity Market; Spot Prices; Wind and Solar Power Dynamics; Structural Vector Autoregressive Model; Structural Impulse Response Functions